The Influence of Work Discipline, Organizational Climate, and Perceived Organizational Support on Organizational Citizenship Behavior Employees of PT Citra Baru Steel - Janiah, Samrotul; Riyanto, Setyo (Archives of Business Research, 2021)
This study examines the effect of work discipline, organizational climate, and perceived organizational support on Organizational Citizenship Behavior. This study's population were employees of PT Citra Baru Steel, a private company engaged in the steel-making industry in Serang City, Banten. By using the nonprobability sampling method obtained 269 samples. The results showed that work discipline had a significant effect on Organizational Citizenship Behavior. Organizational climate has a significant effect on Organizational Citizenship Behavior. Perceived Organizational Support has no significant effect on Organizational Citizenship Behavior, while Work Discipline, Organizational Climate, and Perceived Organizational Support simultaneously positively affect Organizational Citizenship Behavior.